Fontes de nutrientes induzem o crescimento e a produção de óleo essencial em plantas de hortelã peluda (Mentha suaveolens Ehrh.) - Silva, Iberê Martí Moreira da (2017)
The hairy mint (Mentha suaveolens Ehrh.) Is a perennial herbaceous plant of the Lamiacea family, which produces an essential oil (OE), which is used by industries and in popular medicine. Mint cultivation is an alternative to diversify and increase income in Family Agriculture. Agroecology techniques, among them organic fertilization, are recommended for the production of medicinal plants, and the nutrient source is important for growing mint. The main sources of nutrients used in Brazil are cattle and poultry manure. But Bokashi and marine bioclastic granulates (GBM) can be used in the cultivation of medicinal, aromatic and condiment plants. This study analyzed the growth and yield of OE of hairy mint plants (Mentha suaveolens Ehrh.), Submitted to fertilization with EL-Bokashi and Natural Mineral Organ Fertilizer (FOMN), which has the GBM of Lithothamnium calcareous algae in its formulation. Experiments were carried out in a nursery with sombrite and another in a greenhouse, conducted in 3 L pots, in a standard substrate with soil and sand (2: 1), fertilized with organic compounds, in different combinations and at different times of the plant. Plant growth and yield and OE content analyzes were performed. The fertilization with organic compound EL-Bokashi promoted greater growth and accumulation in dry biomass in hairy mint plants at different harvesting times and in a linear manner with increasing doses. The plants fertilized with FOMN showed higher yield of OE at the different doses and harvesting times. The plants that were cultivated in the EL-Bokashi + FOMN blend presented higher biomass and higher OE content, showing a favorable performance of these compounds for the production of hairy mint OE. The use of Bokashi and FOMN is an alternative for producing OE in hairy mint.